Using Electronic Dental Records to Assess Osteoradionecrosis Risk in Irradiated Head and Neck Cancer. (July 2023) - Saenthaveesuk, P.; Kiat-amnuay, S.; Walji, M.F.
Objective: Over the last 2 decades, investigations have demonstrated a decreased trend in the likelihood of osteoradionecrosis of the jaw (ORNJ) after extraction. The aim of this study was to explore the potential risk factors for ORNJ in irradiated head and neck cancer by using patients' electronic dental records (EDRs). Methods: Patients diagnosed with head and neck cancer who had irradiation between January 2010 and December 2020 were included in this retrospective cohort analysis. Patient charts showing evidence of "head and neck cancer, " "oral cancer, " "radiotherapy, " "radiation, " and "oral complication" were identified by an informatics analyst querying the EDR. Subsequently, the charts were manually reviewed, and data quality was assessed on 3 dimensions: completeness, accuracy, and consistency. The patient, tumor, systemic condition/drug, oral condition, treatment/trauma, and radiation were all categorized as potential risk factors. Results: A total of 359 patients were included. With the exception of radiation-related factors, we found that the data quality was generally sufficient to support the research. Multivariate logistic regression analysis demonstrated that the following factors were significant in predicting the occurrence of ORNJ development in irradiated head and neck cancer: smoking (odds ratio [OR], 9.0; 95% CI, 1.9 to 43.0;P = 0.006), steroid use (OR, 6.4; 95% CI, 1.3 to 30.8;P = 0.021), oral health status (OR, 23.7; 95% CI, 2.7 to 211.0;P = 0.005), and postirradiation extraction (OR, 3.8; 95% CI, 1.0 to 14.4; P = 0.050). Conclusions: A 10-y retrospective analysis of data from an EDR revealed that smoking, steroid use, poor oral status, and postirradiation extraction are all factors linked to an increased risk of developing ORNJ. The quality of EDR data may be systematically assessed by determining the completeness, accuracy, and consistency of the underlying data. Radiation-related factors in particular were poorly documented, highlighting the need for collecting or incorporating this information into the EDR. Knowledge Transfer Statement: EDRs can be used to identify risk factors for developing ORNJ in irradiated head and neck cancer and can help clinicians with selecting treatments by incorporating risk and complication considerations.